Strategies for Improving Effective Communication and Patient Safety with SBAR among Healthcare Teams in Hospitals: A Systematic Review - Fajriyah, Novita; Wijaya, Hermanto; Mamesah, Marline Merke; Marga, Irawati (Journal of Health Management Research, 2023)
Background: Ineffective communication between a team of health workers will certainly have an impact on the success of treatment and cause side effects for patients. Adverse events are often analyzed to illustrate the impact of patient safety on quality of care. The side effects referred to are injuries caused by medical behavior that result in prolonged hospitalization and/or disability upon patient discharge. Objective: This systematic review aims to identify the effectiveness of strategies to improve effective communication and patient safety with SBAR among healthcare teams in hospitals. Methods: A systematic review of quantitative and qualitative studies with narrative synthesis. Literature search was sourced from three databases (Medline, CINAHL, and Science Direct) between September 2019 – March 2022. Participants A variety of health professionals including nurses and doctors. Results: The actions required when using the SBAR tool are as follows: situation, briefly state the problem, briefly present background information relevant to the situation, assess, provide analysis and consider various options, and recommend a specific course of action or treatment. Conclusion: This review found evidence that to improve effective communication and patient safety through the application of SBAR, especially when used to provide services to patients in hospitals, especially for emergency, urgent and time-sensitive actions. However this evidence is limited to certain circumstances such as telephone communication.